Restaurateurs and diners responsiveness toward smart card usage in restaurants / Zurena @ Rena Shahril - Shahril, Zurena @ Rena (2016)
With the general thrust of developments and in line with technological advancement and demands of the economy, the payment systems have gone through incredible revolutions. This scenario is offering greater competence and expediency to customers and businesses and the growth in technology without an exception of food and beverage industry has played a vital role in changing diners' payment habits. The availability range of payment services in the restaurants today including the smart card in response to diverse market demands of the changing behaviour and lifestyle of the diners significantly influence their actual usage behaviour. Nevertheless, although smart cards are viewed as a promising and enabling technology, their levels of acceptance and usage have not been at its peak in the Malaysian restaurant industry. This study is empirically investigating restaurateurs and diners responsiveness toward "Touch 'n Go" smart card usage in Malaysian restaurant sector. In integrating, entwining the issues or to facilitate the research problems and the findings both quantitative and qualitative approaches were opted. The insight on the issues was obtained through the interview with 6 restauranteurs while the deeper understanding is validated through self-administered survey among the 400 restaurant diners. With the various statistical analyses ranging from descriptive, inferential and SEM Partial Least Square used to answer the research objectives, questions and hypotheses, some useful insights pertaining to the issues investigated was significantly obtained. The restaurateurs acknowledged that the "Touch 'n' Go" company needs to create more awareness of the public from simply sees this payment card as the only mode of paying for the public transportation but goes beyond on it application including in the restaurants sector. With that, the service providers should aggressively take a positive action by recommending and encouraging the restaurateurs to intensify their promotion of this payment services. An interesting aspect and the most remarkable findings is also drawn from the quantitative analysis that the awareness and brand image in addition to perceived usefulness, ease of use and trust strongly moderate diners in using the "Touch 'n Go" card. This result in fact corresponded well with the proposed study model and strengthened the Theory of Reasoned Action, the Theory of Planned Behavior and the Technology Acceptance Model as the underpinning theories for this study. It was also found that simply making people aware of the smart card and its availability in the restaurants will not necessarily increase the usage without increasing the trust and changing the attitudes of the users which manifest that social marketing campaign may be the best way of uplifting the awareness. In addition, it is interesting to note that the perceived trust as the predictor to awareness, brand image and the actual usage behavior manifestly impart novel and new contribution not only to the restaurants, foodservice operations but to the growing body of literature as well. Finally, findings flow from this study dealing with the smart card technology obviously provides valuable insight to the academicians and practitioners including the major stakeholders, restaurateurs and diners as the end user.